Old stories and contemporary issues in films about antiquity and the Middle Ages - Berto, Luigi Andrea, author.
1 online resource
Keywords: "This volume creates awareness among spectators about the differences between the past and the present, the importance of understanding the past-present relationship, and the reasons behind reconstructions that distort the past in films about Antiquity and the Middle Ages. Old Stories and Contemporary Issues in Films about Antiquity and the Middle Ages is useful for undergraduates, postgraduates, and scholars interested in the Antiquity and Middle Ages, the relationship between films and history, and modern uses of the past"--